Software architecture in practice. - Bass, Len, ....-; Clements, Paul, 1955-; Kazman, Rick, ....- (Boston : Addison-Wesley, 2008)
Introducing the fundamental concepts and identifying best practices in the field, this textbook explains the role of software architecture in achieving system quality, its importance for a company's business strategy, and the specifics of how software is structured and how its components interact. Technical topics related to the design, specification, and validation of a system are detailed, with particular attention to the relevance of a project's business context. Case studies profiling successful architecture illustrate key points in both the technical and the organizational discussion. The authors are software engineers.